Short review on solar neutrinos experiments and search for sterile neutrinos with solar neutrino detectors - Pallavicini Marco (EPJ Web of Conferences, 2015)
The spectroscopy of solar neutrinos is now entering the precision era, after a golden age which has led to the discovery of neutrino oscillations and the MSW effect. In this paper we summarise the current experimental knowledge in the field and its future perspectives, showing that solar neutrino detectors are and will remain a crucial tool for a deeper understanding of stars, neutrinos, and fundamental physics. We also show that solar neutrinos may become pivotal for the search of sterile neutrinos.